Pengembangan Media Pembelajaran Digital untuk Meningkatkan Pemahaman dan Kreativitas pada Peserta Didik Kelas II Sekolah Dasar dengan Model ADDIE - Intan Januarisa Setyawati Fermansyah; Mariana Natje Aurora Leonny Rumbiak; Daniel Mickoy Verioga; Andreas Erwin Prasetya (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to develop digital learning media based on Canva and Wordwall to enhance students’ conceptual understanding and creativity in the topic of plane geometry in second-grade elementary school mathematics. The issue addressed arises from the limited integration of technology in classroom learning, despite the availability of digital infrastructure such as projectors. The research applied a Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Conducted at SD Kanisius Demangan Baru, Canva was utilized to design visually engaging instructional materials, while Wordwall supported game-based interactive learning activities. Data collection involved observations, interviews, pre-tests, post-tests, and expert validation. Additionally, a Participatory Action Research (PAR) approach was employed to engage both teachers and students in media refinement and feedback. Results showed that the developed media met high validity standards and significantly improved students’ understanding and creativity. These findings support the effectiveness of Canva and Wordwall as digital tools developed through R&D and the ADDIE model to enhance active and enjoyable mathematics learning in primary schools.